(3TQM cGajI GHf GdMGLHs - (3YR GdOjf YHO GdYRjR Hf LeYI Hf RjO GdfMhi GdeTghQ HGHf GdbhGSs; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s ((3MjOQ Hf eMeO GdYeGd GdeOYh fXGe GdCUagGfi s)
(3ChdgG (B:s
(3bGd GdTjN GdMeO ddg GdCRdi GdefGf GdCHOi GdOjGf hHYO aEfg deG cGf cJGH GdcGajI ef JUGfja GdTjN GdeGdci s
(3BNQgG (B:s
(3hdG jNai Ydjc MceI eY GdeYJd eWdbkG hGdeVGYa agPG eG JjSQ di ef TQM gPG GdcJGH s
(3HHYV ChQGbgG CKQ JbWjYs
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1370s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs